ANALISA APLIKASI CHATBOT UNTUK PERTANYAAN UMUM TERKAIT UNIVERSITAS DI UNIVERSITAS XYZ - Herman Herman; Andik Yulianto; Stephani Lim (Program Studi Pendidikan Informatika, Universitas Citra Bangsa, 2023)
Technology has become an integral part of modern life. Especially in marketing, technologies such as social robots and chatbots are often used to provide information about companies, products, and services to users. These chatbots are built using the Successive Approximation Model (SAM) with PHP and JavaScript programming languages, and use PhpMyAdmin as a means of database management. This research aims to determine user responses and the influence of variables on compatibility, perceived usefulness, perceived ease of use, behavioral intention, and actual use of the VA XYZ chatbot using the TAM approach. This study uses an experimental method with 180 respondents. The results of the analysis show that compatibility affects perceived usefulness and perceived ease of use, perceived ease of use affects perceived usefulness and behavioral intention, perceived usefulness does not significantly affect behavioral intention, and behavioral intention does not significantly affect actual use.